Effect of pH Value on the Corrosion Behavior of X100 Pipeline Steel in Simulated Seawater - QI Bin, LI Jidong, ZHANG Ying, CHEN Dongxu, HUANG Xinglin, WANG Yiyong (Cailiao Baohu)
pH value is one of the important factors affecting corrosion in marine environment.The effects of pH value on the corrosion behavior of X100 pipeline steel in simulated seawater were investigated using kinetic potential polarization curves，electrochemical impedance spectroscopy testing technology，corrosion weight loss measurement method，and scanning electron microscopy (SEM) morphology analysis method.Results showed that as the pH value of simulated seawater increased from 7.5 to 9.0，the corrosion rate of X100 pipeline steel showed a trend of increasing first and then decreasing.The anodic region of the kinetic potential polarization curve exhibited a stable passivation interval at pH values of 7.5，8.0 and 8.5.However，when the pH value increased from 7.5 to 8.0，the corrosion rate accelerated significantly.When pH＝8.0，the corrosion potential of X100 pipeline steel became more negative，the corrosion current density was highest，the capacitive arc was smallest，and the corrosion rate reached its maximum.Furthermore，the corrosion products on the substrate surface were thicker，and the corrosion was more severe.When pH＝9.0，the dynamic potential polarization curve showed a clear transition from the dissolution region to the passivation region in the anodic region，with a distinct over-passivation zone.However，when the pH value increased from 8.0 to 9.0，the corrosion phenomenon gradually alleviated，and the corrosion rate decreased instead.